Environmental impact of energy strategies within the EEC : a report prepared for the Environment and Consumer Protection Service of the Commission of the European Communities (Published for the Commission of the European Communities, by Pergamon Press, 1980)
Environmental Impact of Energy Strategies within the EEC is a report prepared for the Environment and Consumer Protection Service of the Commission of the European Communities. The report aims to examine the effects on the environment of the production and use of different forms of energy within the community and to determine the scope for minimizing environmental impact through the adoption of appropriate energy strategies. After an introduction, this report presents in Sections 2 and 3 the summary, conclusions, and recommendations presented at the time of the Nuclear Hearings. The main body.